Determination of free chlorine concentration and pH of the water using neural network based colorimetric method - Yaman, Suleyman; Karasekreter, Naim; Ergun, Ucman (Springer Int Publ Ag, 2022)
The free chlorine concentration and pH of the water must be constantly monitored and controlled for reasons such as disinfection effectiveness, operational monitoring, and public health. In this study, a novel, user-friendly, cost-effective, and the portable system was developed that can determine the free chlorine concentration and pH of water rapidly and with high accuracy by digital image processing-based colorimetric method. The proposed system is based on capturing the image of the occurred color change by adding an indicator to the water samples and analyzing it with an artificial neural network and digital image processing techniques. According to the measurement results obtained from the developed system, it was found that the proposed method has an accuracy of 99.71% for free chlorine concentration and 99.69% for pH value. The results obtained were discussed with other studies in the literature and showed that the proposed method can be used in the determination of free chlorine concentration and pH in drinking water, swimming pools, well waters, and aqua parks.
Keywords: Colorimetric method; Digital image processing; Free chlorine; pH; Artificial neural network